Volatile organic compounds from Bacillus subtilis BE6 inhibit and lyse mycelial growth of Sclerotium rolfsii - SITI HARDIYANTI; WIDI AMARIA; SRI RAHAYUNINGSIH; SUPRIADI SUPRIADI; WARTONO WARTONO; RITA HARNI; ELI KORLINA; WIDODO WIDODO; MOHAMAD ANA SYABANA; RUSBIANTO WIJAYA (Asian Journal of Agriculture, 2026)
Abstract. Hardiyanti S, Amaria W, Rahayuningsih S, Supriadi, Wartono, Harni R, Korlina E, Widodo, Syabana MA, Wijaya R. 2026. Volatile organic compounds from Bacillus subtilis BE6 inhibit and lyse mycelial growth of Sclerotium rolfsii. Asian J Agric 10 (1): g100123. https://doi.org/10.13057/asianjagric/g100123. Sclerotium rolfsii is a devastating soil-borne pathogen responsible for significant crop losses worldwide, highlighting the need for effective control strategies. Antagonistic bacteria provide an eco-friendly biocontrol alternative for managing such plant diseases. This study evaluated the antifungal efficacy of Volatile Organic Compounds (VOCs) produced by eight bacterial isolates belonging to the genera Bacillus, Serratia, Brucella, and Burkholderia against S. rolfsii under in vitro conditions. Antifungal activity was assessed using a dual-culture assay in divided petri dishes, followed by Scanning Electron Microscopy (SEM) to assess morphological changes, and headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME/GC-MS) for chemical profiling. Among the isolates, indigenous Bacillus subtilis BE6 exhibited the strongest inhibitory effect on S. rolfsii isolate Sc.lb, achieving a growth inhibition rate of 57.2±10.5% compared to the control. Other notable isolates included Bacillus amyloliquefaciens P7 (43.5±7.3%) and Serratia surfactantfaciens S108 (42.7±10.9%). Observation through SEM demonstrated that VOCs from B. subtilis BE6 induce severe hyphal abnormalities, such as shrinkage, wrinkling, and lysis. GC-MS analysis identified 27 VOCs emitted by B. subtilis BE6, with the dominant compounds being cis-2,3-epoxybutane (27.34%), methyl (Z)-N-hydroxybenzenecarboximidate (17.19%), 5-methyl-2-hexanone (14.10%), hexanal (12.46%), and 2,5-dimethylpyrazine (2.89%). These compounds belong to the aldehyde, epoxide, oxime, ketone, and pyrazine groups, all of which are associated with antimicrobial properties. Overall, the results demonstrate that VOCs produced by B. subtilis BE6 effectively inhibit and disrupt the mycelial growth of S. rolfsii, highlighting their potential as eco-friendly biofumigant agents for the managing of soil-borne plant diseases. Further studies are required to validate their efficacy under in vivo and field conditions, as well as to elucidate the individual and synergistic roles of key VOCs.